Modeling the precipitation kinetics in systems with strong heterophase fluctuations - Turkin, A.A.; Bakai, A.S. (Вопросы атомной науки и техники, 2007)
The hierarchy of the Becker-Döring rate equations is used to consider the influence of heterophase fluctuations on the kinetics of precipitation in supersaturated solid solutions, including the nucleation stage and the crossover to the final Ostwald ripening regime. Numerical simulation shows that a quasi-stationary distribution of solute clusters forms in the region of small sizes. This population of small clusters (heterophase fluctuations) is separated by a gap from the distribution of coarsening precipitates. The scaling behaviour of the precipitate size distribution during the later stage of decomposition is consistent with the Lifshits-Slyozov theory of coarsening.